LC30 concrete prepared from light ceramsite and preparation method of LC30 concrete
By using high-belitt sulfaluminate cement and thickener in ceramic concrete, the problems of ceramic uplift and early insufficient strength are solved, and the efficient uniform distribution and strength improvement of ceramic concrete are achieved.
Patent Information
- Application Number
- CN202411854988.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-11
AI Technical Summary
During the pouring process, ceramic concrete is easy to float due to its small density, resulting in insufficient local density, affecting the mechanical properties of the structure; its low strength and insufficient early strength limits the application range and construction convenience.
High Belite sulfaluminate cement is mixed and stirred with clay to form a pre-set cement slurry, increasing the density of the clay surface and reducing the floating phenomenon; at the same time, thickening agents are used to cooperate with carboxylic acid water reducers to optimize the working performance and clay distribution of concrete.
It effectively reduces the floating phenomenon of ceratops, improves the early strength and uniform distribution of ceratops concrete, enhances crack resistance and workability, and is suitable for a wider range of engineering applications.
Smart Images

Figure BDA0005191566480000031 
Figure BDA0005191566480000061 
Figure BDA0005191566480000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete and relates to LC30 concrete made of lightweight ceramsite and a preparation method thereof. Background Art
[0002] As the country's requirements for energy conservation and environmental protection in the construction industry continue to increase, the design of house structures has gradually shifted towards reducing deadweight, energy conservation and emission reduction. Against this background, ceramsite concrete has emerged as a new type of lightweight material and has gradually become an indispensable part of modern construction projects. The bulk density of ceramsite concrete ranges from about 800kg / m 3 Up to 1900kg / m 3 The weight of ceramsite concrete is much lower than that of traditional concrete, which greatly reduces the overall weight of the building without sacrificing structural strength. Ceramsite concrete is mainly composed of light aggregates such as ceramsite and ceramsite sand, powder materials including cement and fly ash, fine aggregates such as sand, appropriate amount of water, admixtures and thickeners. This combination gives ceramsite concrete many superior properties, such as light weight, good thermal insulation and sound insulation, excellent fire resistance, etc. Therefore, it is widely used in the construction of non-load-bearing internal partition walls, and its bearing capacity can be enhanced by built-in steel bars, which is suitable for external wall structures such as schools and dormitories.
[0003] Ceramic aggregate concrete wall panels not only have the advantages of low thermal conductivity, high strength, good fire resistance and good impermeability, but also reduce transportation costs and installation difficulties due to their lightweight characteristics, providing an ideal solution for green buildings. However, in the application and development of ceramsite concrete, some problems that need to be solved have also been encountered. First, due to the low density of lightweight aggregates such as ceramsite, it is easy to float during the pouring process, resulting in insufficient local density of concrete, thus affecting the mechanical properties of the entire structure. This problem not only limits the scope of use of ceramsite concrete, but also increases the uncertainty in the construction process. Secondly, ceramsite concrete currently made of lightweight ceramsite generally uses foaming technology to prevent it from floating. The increase in gas in the concrete causes the bulk density of ceramsite concrete to decrease, which greatly reduces its strength. The ceramsite concrete exterior wall panels made by foaming technology are generally only used for partitions or decoration due to their low strength. In order to improve the strength of ceramsite concrete exterior wall panels made of lightweight ceramsite and expand its application areas, reducing water consumption is a common method, but this brings new challenges: reducing water will lead to a decrease in the fluidity and workability of concrete, which will bring inconvenience to on-site construction, especially when a good filling effect needs to be ensured. Finally, the early strength of ceramsite concrete is low, especially during transportation and installation within 7 days, slight bumps can easily cause cracks and corner loss, which seriously affects the quality of the finished product. Therefore, although ceramsite concrete with ordinary proportions has shown many advantages, its proportion and production process still need to be improved to meet the needs of a wider range of engineering applications. Summary of the invention
[0004] The purpose of the present invention is to solve the above problems existing in the prior art and to provide a LC30 concrete made of lightweight ceramsite with low bulk density, good crack resistance, good workability and uniform ceramsite distribution.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] The invention discloses LC30 concrete made of lightweight ceramsite, wherein the ceramsite concrete comprises the following raw materials in parts by weight: 50-70 parts of high-belite sulphoaluminate cement, 340-380 parts of ordinary Portland cement, 100-150 parts of fly ash, 230-250 parts of ceramsite, 300-340 parts of pottery sand, 300-340 parts of machine-made sand, 1-3 parts of polypropylene fiber, 8-10 parts of water reducer, 0.1-0.25 parts of thickener and 170-190 parts of water.
[0007] In the above-mentioned LC30 concrete made of lightweight ceramsite, the density of high belite sulphoaluminate cement is 3100-3200kg / m 3 , initial setting time 10-20min, final setting time 55-65min, containing the following mass percentages of substances: 18-20wt% SiO2, 15-16wt% Al2O 3、 1-2wt% Fe2O3, 40-45wt% CaO, 3.5-4.5wt% MgO, 10-11wt% SO3. The high-belite sulphoaluminate cement of the present invention is mixed and stirred with ceramsite and left to stand for 15 minutes to produce a layer of cement paste on the surface of the ceramsite. The paste has been initially set and is not easily washed away during subsequent stirring. The paste and the ceramsite form a density of about 1200kg / m 3 The irregular spherical material has a higher density than the expanded clay itself, which greatly reduces the floating phenomenon of expanded clay.
[0008] As a preference, ordinary Portland cement has a density of 3000-3200 kg / m 3 Bulk PO42.5 silicate cement with an initial setting time of not less than 45 minutes and a final setting time of not more than 390 minutes.
[0009] Preferably, the density of fly ash is 2100-2300 kg / m 3 , containing the following substances in percentage by mass: 45-55wt% SiO2, 35-45wt% Al2O3, 2-8wt% Fe2O3, 5-15wt% CaO, 0.1-1.5wt% MgO.
[0010] In the above-mentioned LC30 concrete made of lightweight ceramsite, the particle size of the ceramsite is 5-15 mm and the density grade is 500-600.
[0011] In the above-mentioned LC30 concrete made of lightweight ceramsite, the particle size of the ceramsite is 1-5 mm and the density grade is 600-700.
[0012] In the above-mentioned LC30 concrete made of lightweight ceramsite, the length of polypropylene fiber is 9-12mm and the apparent density is 950-1000kg / m 3 The addition of polypropylene fiber can increase the crack resistance of ceramsite concrete and prevent large-scale concrete shedding caused by bumps.
[0013] The present invention needs to strictly control the particle size of ceramsite sand. The particle size is too large, resulting in more gaps inside the concrete, which will not only affect the strength of the concrete, but also reduce its impermeability and frost resistance. At the same time, the particle size of ceramsite sand is too large, which will increase the floating amount of ceramsite sand, resulting in a decrease in the homogeneity of the concrete, and there will be too much ceramsite sand on the upper part of the molding surface and too little ceramsite sand on the lower part. If the particle size of ceramsite sand is too small, it will not be able to form an aggregate framework, and it will also cause an increase in water consumption, thereby affecting the workability and strength of ceramsite concrete. In combination with actual conditions and material cost, it is selected that the ceramsite particle size is 5-15mm, and the ceramsite sand particle size is 1-5mm. Considering the three factors of strength, homogeneity and cost, it is decided to adopt a polypropylene fiber with a length of 9-12mm as one of the raw materials of the ceramsite concrete.
[0014] In the above-mentioned LC30 concrete made of lightweight ceramsite, the thickener has the structural formula shown below:
[0015]
[0016] The thickener used in the present invention can produce a good synergistic effect with the carboxylic acid series water reducer, further optimizing the working performance of the concrete. The water retention performance of the thickener is not affected by temperature changes, and it can still maintain high efficiency under high temperature conditions (temperature resistance range can reach 130°C to 150°C), which is significantly better than traditional cellulose ether products such as CMC (carboxymethyl cellulose) and HPMC (hydroxypropyl methylcellulose). Most thickeners are very sensitive to the dosage. If the dosage is too low, the slurry viscosity is insufficient, and the problems of water seepage and segregation cannot be effectively improved; on the contrary, if the dosage is too high, although the viscosity can be increased, the fluidity of the concrete will be deteriorated, affecting the construction operation, and may cause poor material density, thereby affecting the final concrete quality. The present invention controls the amount of thickener added, so that the ceramsite concrete has good pseudoplasticity and water retention, and the slump loss has little effect over time, which greatly improves the working performance, and increases the viscosity of the ceramsite concrete, solving the problem of some ceramsite floating.
[0017] In the above-mentioned LC30 concrete made of lightweight ceramsite, the water reducing agent is a carboxylic acid water reducing agent with a solid content of 5-15%.
[0018] The present invention also provides a method for preparing the LC30 concrete made of the above-mentioned lightweight ceramsite, the method comprising the following steps:
[0019] S1, prepare the above raw materials;
[0020] S2, dissolving the thickener in 25-35 wt % water and stirring evenly to obtain a thickener solution;
[0021] S3, stirring the thickener solution, 25-35wt%, 55-75wt% water reducer, high belite sulphoaluminate cement, fly ash and ceramsite, and then leaving it to stand;
[0022] S4, adding ordinary Portland cement, ceramic sand and polypropylene fiber and stirring, and then adding machine-made sand, the remaining 30-50wt% of water, and 25-45wt% of water reducing agent and stirring thoroughly to obtain concrete mortar;
[0023] S5, placing concrete mortar into a mold, casting and molding, and then curing to obtain ceramsite concrete.
[0024] The present invention firstly mixes the thickener with water in proportion to form a thickener solution, so as to prevent the thickener from being insoluble in water and forming a block-like object that affects its function. Secondly, through the characteristic of short initial setting time of high belite cement, a mortar protective layer with certain properties and strength is formed with the surface of ceramsite in a short time, and the protective layer is not suitable to be washed away by other substances during the subsequent stirring process. The density of the composition is greater than the density of the ceramsite itself, which effectively reduces the floating phenomenon of the ceramsite. Polypropylene fiber is mixed with dry pottery sand. This method makes the fiber easier to be broken up and evenly dispersed, avoiding the problem that the fiber is difficult to disperse after being wetted with a large amount of water. Finally, other raw materials are added and fully stirred to form ceramsite concrete with small slump loss, plastic wall, uniform distribution of ceramsite, and high initial strength.
[0025] In the above-mentioned method for preparing LC30 concrete made of lightweight ceramsite, the standing treatment time of step S3 is: until the high-belite sulphoaluminate cement is initially set and the ceramsite is completely formed into a spherical substance.
[0026] In the above-mentioned method for preparing LC30 concrete made of lightweight ceramsite, the curing conditions can be carried out according to the existing conditions, and standard curing, equal curing, steam curing and other methods can be carried out.
[0027] Preferably, the standard curing temperature is 20±2°C and the relative humidity is 95%.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention combines the characteristics of high-belite sulphoaluminate cement with short initial setting time and high early strength to improve the production process of ceramsite concrete. The ceramsite concrete is mixed and stirred with the cement in an advanced manner. After the cement is initially set, it forms a density of about 1200kg / m 3 The irregular spherical objects are not easily washed away during subsequent mixing, and their density is higher than that of the original expanded clay, which reduces the possibility of floating, making the expanded clay concrete more uniform. At the same time, it increases the early strength of the expanded clay concrete after molding, and effectively reduces the concrete falling off caused by insufficient strength during the installation and transportation of the early components.
[0030] 2. The thickener added in the present invention has excellent water retention capacity and strong adhesion, which helps to reduce the floating of lightweight aggregates and solve the common pain points of ceramsite concrete using lightweight ceramsite. Compared with traditional cellulose ether thickeners, the thickener added in the present invention has a reducing effect on the bulk density of ceramsite concrete but the amplitude is small, while ensuring that the impact on the strength of concrete is small, which helps to maintain the stability of material properties. It remains stable when the temperature changes, ensuring the reliability and consistency of ceramsite concrete under different environmental conditions. Good plasticity and small slump loss within 30 minutes are very suitable for the environmental conditions of actual on-site construction.
[0031] 3. The present invention proposes a ceramsite concrete mix ratio made of lightweight ceramsite with a compressive strength of more than 30 MPa, good crack resistance, good workability, and uniform ceramsite distribution, which is of great help to engineering construction and quality improvement of ceramsite concrete components. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A cross-sectional view of the ceramsite concrete prepared in Example 1;
[0033] Figure 2 A cross-sectional view of the ceramsite concrete prepared in Example 2;
[0034] Figure 3 This is a cross-sectional view of the ceramsite concrete prepared in Comparative Example 1;
[0035] Figure 4 This is a cross-sectional view of the ceramsite concrete prepared in Comparative Example 2. DETAILED DESCRIPTION
[0036] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0037] Example 1
[0038] S1, prepare the following raw materials: 60 parts of high belite sulphoaluminate cement, 360 parts of ordinary Portland cement, 120 parts of fly ash, 240 parts of ceramsite, 320 parts of pottery sand, 310 parts of machine-made sand, 1.5 parts of polypropylene fiber, 8.5 parts of water reducer, 0.14 parts of thickener, and 180 parts of water;
[0039] The density of high belite sulphoaluminate cement is 3150kg / m 3 , initial setting time 15min, final setting time 60min, containing the following mass percentages of substances: 18.89wt% SiO2, 15.78wt% Al2O 3、 1.4wt% Fe2O3, 43.9wt% CaO, 3.94wt% MgO, 10.6wt% SO3, the balance being unavoidable impurities;
[0040] PO42.5 ordinary Portland cement has a density of 3100kg / m 3 , initial setting time is 50min, final setting time is 360min. ;
[0041] The density of fly ash is 2220kg / m 3, containing the following substances in percentage by weight: 46.44wt% SiO2, 38.01wt% Al2O3, 3.12wt% Fe2O3, 7.5wt% CaO, 0.23wt% MgO, and the remainder being unavoidable impurities;
[0042] Both ceramsite and clay sand are in saturated surface dry state, with an average particle size of 8mm and a density grade of 600 for ceramsite, and an average particle size of 3mm and a density grade of 700 for clay sand;
[0043] The moisture content of machine-made sand is 10%;
[0044] The average length of polypropylene fiber is 10mm and the apparent density is 980kg / m 3 ;
[0045] The water reducer was a carboxylic acid water reducer purchased from Beijing Zhongshuike Company, with a solid content of 10%;
[0046] The thickener has the structural formula shown below:
[0047]
[0048] S2, dissolving the thickener in 30 wt % water and stirring uniformly to obtain a thickener solution;
[0049] S3, stirring the thickener solution, 30wt% water, 60wt% water reducer, high belite sulphoaluminate cement, fly ash and ceramsite for 2.5min, and then standing for 15min to allow the high belite sulphoaluminate cement to initially set and form irregular spherical objects with certain properties with the ceramsite;
[0050] S4, adding ordinary Portland cement, pottery sand and polypropylene fiber and stirring, and then adding machine-made sand, the remaining 40wt% of water and 40wt% of water reducing agent and stirring for 1.5min to obtain concrete mortar;
[0051] S5. After the mortar is cast and formed, it is cured to obtain ceramsite concrete, wherein the curing specifically comprises: demolding the ceramsite concrete 35 hours after it is formed, and placing it in a standard curing room with a temperature of 20° C. and a relative humidity of 95% after demolding.
[0052] Embodiment 2:
[0053] S1, prepare the following raw materials: 60 parts of high belite sulphoaluminate cement, 360 parts of ordinary Portland cement, 120 parts of fly ash, 240 parts of ceramsite, 320 parts of pottery sand, 310 parts of machine-made sand, 1.5 parts of polypropylene fiber, 8.5 parts of water reducer, 0.14 parts of thickener, and 180 parts of water;
[0054] The density of high belite sulphoaluminate cement is 3150kg / m 3, initial setting time 15min, final setting time 60min, containing the following mass percentages of substances: 18.89wt% SiO2, 15.78wt% Al2O 3、 1.4wt% Fe2O3, 43.9wt% CaO, 3.94wt% MgO, 10.6wt% SO3, the balance being unavoidable impurities;
[0055] PO42.5 ordinary Portland cement has a density of 3100kg / m 3 , initial setting time is 50min, final setting time is 360min. ;
[0056] The density of fly ash is 2220kg / m 3 , containing the following substances in percentage by weight: 46.44wt% SiO2, 38.01wt% Al2O3, 3.12wt% Fe2O3, 7.5wt% CaO, 0.23wt% MgO, and the remainder being unavoidable impurities;
[0057] Both ceramsite and clay sand are in saturated surface dry state, with an average particle size of 8mm and a density grade of 600 for ceramsite, and an average particle size of 3mm and a density grade of 700 for clay sand;
[0058] The moisture content of machine-made sand is 10%;
[0059] The average length of polypropylene fiber is 10mm and the apparent density is 980kg / m 3 ;
[0060] The water reducer was a carboxylic acid water reducer purchased from Beijing Zhongshuike Company, with a solid content of 10%;
[0061] The thickener has the structural formula shown below:
[0062]
[0063] S2, dissolving the thickener in 30 wt % water and stirring uniformly to obtain a thickener solution;
[0064] S3, uniformly stirring and mixing the thickener solution and the remaining raw materials to obtain concrete mortar;
[0065] S5. After the mortar is cast and formed, it is cured to obtain ceramsite concrete, wherein the curing specifically comprises: demolding the ceramsite concrete 35 hours after it is formed, and placing it in a standard curing room with a temperature of 20° C. and a relative humidity of 95% after demolding.
[0066] Comparative Example 1:
[0067] The only difference from Example 1 is that no thickener is added.
[0068] Comparative Example 2:
[0069] S1, 420 parts of ordinary Portland cement, 120 parts of fly ash, 240 parts of ceramsite, 320 parts of ceramic sand, 310 parts of machine-made sand, 1.5 parts of polypropylene fiber, 8.5 parts of water reducer, 0.14 parts of thickener, and 180 parts of water;
[0070] Ordinary Portland cement is PO42.5 Shunjiang bulk cement;
[0071] The ceramsite sand is in a saturated surface dry state, with an average particle size of 8mm and an apparent density of 833kg / m 3 The average particle size of the ceramic sand is 3mm and the apparent density is 909kg / m 3 ;
[0072] The moisture content of machine-made sand is 10%;
[0073] The average length of polypropylene fiber is 10mm and the apparent density is 980kg / m 3 ;
[0074] The water reducer was a carboxylic acid water reducer purchased from Beijing Zhongshuike Company, with a solid content of 10%;
[0075] The thickener has the structural formula shown below:
[0076]
[0077] S2, dissolving the thickener in 30 wt % water and stirring uniformly to obtain a thickener solution;
[0078] S3, stirring the thickener solution, 30wt% and 60wt% water reducer, high belite sulphoaluminate cement, fly ash and ceramsite for 2.5min, and then standing for 15min to allow the high belite sulphoaluminate cement to initially set and form irregular spherical objects with certain properties with the ceramsite;
[0079] S4, adding ordinary Portland cement, pottery sand and polypropylene fiber and stirring, and then adding machine-made sand, the remaining 40wt% of water and 40wt% of water reducing agent and stirring for 1.5min to obtain concrete mortar;
[0080] S5. After the mortar is cast and formed, it is cured to obtain ceramsite concrete, wherein the curing specifically comprises: demolding the ceramsite concrete 35 hours after it is formed, and placing it in a standard curing room with a temperature of 20° C. and a relative humidity of 95% after demolding.
[0081] The concrete prepared in the above embodiments and comparative examples was tested for slump and slump after 60 minutes, which reflects the working performance of ceramsite concrete over time. A 150mm*150mm*150mm concrete test block was made and its 28d compressive strength was tested. The concrete bulk density was tested to ensure that the thickener had little effect on the bulk density. A 100mm*100mm*100mm concrete test block was made, the test block was cut, and the floating condition of the ceramsite in the cross section was observed.
[0082] Taking the central axis of the cube test block as the boundary, the ratio of the amount of expanded clay in the upper and lower parts of Example 1-2 and Comparative Example 1-2 is compared. The larger the data, the more uneven the upper and lower distribution.
[0083] Table 1: Statistical table of the number distribution of concrete ceramsite prepared in the examples and comparative examples
[0084] Example (Amount of ceramsite in the upper part / Amount of ceramsite in the lower part) - 1 Example 1 0 Example 2 0.38 Comparative Example 1 0.21 Comparative Example 2 0.41
[0085] It can be seen from Table 1 that the ceramsite is most evenly distributed under the combined action of the thickener of the present invention and high belite cement.
[0086] Table 2: Concrete performance test results prepared in Example 1-2 and Comparative Example 1-2
[0087]
[0088] from Figure 1 It can be seen that the early strength characteristics of high-belite cement are used to wrap a layer of cement paste outside the ceramsite, and the outside of the ceramsite is obviously wrapped with white paste. Under the premise of improving the process, combined with thickeners, the uniform distribution of ceramsite in concrete can be effectively promoted, and the number of ceramsite in the upper and lower parts is almost equal. Figure 2 It can be concluded that the cement needs to be left to stand for 15 minutes during the mixing process to wait for the cement to set initially, otherwise the high-belite sulphoaluminate cement will not be effective in improving the uniform distribution of ceramsite, and the ceramsite will not be wrapped with white slurry. Figure 3 It can be seen that the thickener also has a significant effect on improving the uniform distribution of ceramsite concrete. When no thickener is added, the effect is poor compared with Example 1. Figure 4 It can be seen that the distribution of ceramsite is the most uneven among the four pictures, which shows that the effect of high belite sulphoaluminate cement on the anti-floating of ceramsite is better than that of thickener. In summary, both thickener and high belite sulphoaluminate cement have the function of improving the floating of ceramsite, and the effect is better under the synergistic effect of the two. When high belite sulphoaluminate cement is used, it needs to be left to stand for 15 minutes to wait for the cement to initially set to form a white slurry to wrap the ceramsite, so that its anti-floating effect can be reflected, and the anti-floating effect is better than the case of adding thickener alone.
[0089] As can be seen from the results of the above table. The bulk density of the three groups with thickener added is lower than that of the comparative example 1 without thickener added, and the difference between its 28d strength and the group without adding is small. It can be seen that the thickener has the effect of slightly reducing the bulk density of ceramsite concrete, and this effect will not greatly affect its 28d strength, nor will it affect the growth of the early strength of the high-belite sulphoaluminate cement. After adding the thickener, the initial slump of ceramsite concrete will decrease, because the thickener is relatively viscous, which helps the concrete to maintain a specific shape. The slump loss after 60min is significantly less than the group without adding the thickener. It can be seen that the addition of the thickener is of great help to the on-site construction. After adding the high-belite sulphoaluminate cement, the early strength of the concrete increases significantly, and the 28d strength is basically the same as when it is not added. Standing for 15min has a greater impact on the distribution of ceramsite, and has a certain impact on the early strength, but it is still higher than the strength when it is not added. Adding the thickener has a smaller loss over time on the slump of ceramsite concrete, and adding the thickener of the present invention to obtain a small reduction in the bulk density of ceramsite concrete, which meets the requirements of lightweight concrete. Ordinary cellulose ether improves working performance to a certain extent, but has a greater impact on the bulk density of concrete, resulting in greater strength loss.
[0090] In summary, the present invention utilizes a ceramsite concrete thickener, which has good water retention and strong adhesion, and the adhesion and water retention do not change much with temperature. It has good synergistic performance with traditional polycarboxylic acid water-reducing agents. The thickener can effectively reduce the floating of ceramsite, prevent the uneven density of the ceramsite concrete structure, and prevent the phenomenon of local strength weakening. It can react well with the carboxylic acid water-reducing agent to increase the water retention of concrete. Compared with traditional cellulose ether, the thickener can slightly reduce the bulk density of ceramsite concrete, and the reduction effect is not as good as cellulose ether, but the effect on strength is small, and the strength does not change much compared with when it is not added. The ceramsite concrete using the thickener can increase the amount of water-reducing agent appropriately and reduce the amount of tap water, thereby reducing the water-cement ratio and improving the strength of the concrete itself. Due to the excellent water-retention performance, the water-reducing agent will not produce water bleeding after the appropriate amount of water-reducing agent is increased, and the workability of the concrete can be kept small within 30 minutes, which is of great help to on-site construction.
[0091] The parts of the embodiments herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0092] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
[0093] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. An LC30 concrete made of lightweight ceramsite, characterized in that: The ceramsite concrete comprises the following raw materials in parts by weight: 50-70 parts of high-belite sulphoaluminate cement, 340-380 parts of ordinary Portland cement, 100-150 parts of fly ash, 230-250 parts of ceramsite, 300-340 parts of pottery sand, 300-340 parts of machine-made sand, 1-3 parts of polypropylene fiber, 8-10 parts of water reducer, 0.1-0.25 parts of thickener, and 170-190 parts of water.
2. The LC30 concrete made of lightweight ceramsite according to claim 1, characterized in that: The density of high belite sulphoaluminate cement is 3100-3200kg / m 3 , initial setting time 10-20min, final setting time 55-65min, containing the following mass percentages of substances: 18-20wt% SiO2, 15-16wt% Al2O 3、 1-2wt% Fe2O3, 40-45wt% CaO, 3.5-4.5wt% MgO, 10-11wt% SO3.
3. The LC30 concrete made of lightweight ceramsite according to claim 1, characterized in that: The particle size of ceramsite is 5-15mm and the density grade is 500-600.
4. The LC30 concrete made of lightweight ceramsite according to claim 1, characterized in that: The particle size of ceramic sand is 1-5mm and the density grade is 600-700.
5. The LC30 concrete made of lightweight ceramsite according to claim 1, characterized in that: The length of polypropylene fiber is 9-12mm and the apparent density is 950-1000kg / m 3 .
6. The LC30 concrete made of lightweight ceramsite according to claim 1, characterized in that: The thickener has the structural formula shown below:
7. The LC30 concrete made of lightweight ceramsite according to claim 1, characterized in that: The water reducer is a carboxylic acid water reducer with a solid content of 5-15%.
8. A method for preparing LC30 concrete made of lightweight ceramsite as claimed in claim 1, characterized in that: The method comprises the following steps: S1. Prepare the raw materials according to claim 1; S2, dissolving the thickener in 25-35 wt % water and stirring evenly to obtain a thickener solution; S3, stirring the thickener solution, 25-35wt%, 55-75wt% water reducer, high belite sulphoaluminate cement, fly ash and ceramsite, and then leaving it to stand; S4, adding silicate cement, ceramic sand and polypropylene fiber and stirring, and then adding machine-made sand, the remaining 30-50wt% of water, and 25-45wt% of water reducing agent and stirring thoroughly to obtain concrete mortar; S5, placing concrete mortar into a mold, casting and molding, and then curing to obtain ceramsite concrete.
9. A method for preparing LC30 concrete made of lightweight ceramsite according to claim 8, characterized in that: The standing treatment time in step S3 is: until the high-belite sulphoaluminate cement is initially set and the ceramsite is completely formed into a spherical substance.
10. The method for preparing LC30 concrete made of lightweight ceramsite according to claim 8, characterized in that: Maintenance includes one of standard maintenance, equal maintenance, and steam maintenance.